2018
DOI: 10.1096/fj.201800237r
|View full text |Cite
|
Sign up to set email alerts
|

Targeting histone methyltransferase enhancer of zeste homolog‐2 inhibits renal epithelial‐mesenchymal transition and attenuates renal fibrosis

Abstract: Enhancer of zeste homolog-2 (EZH2) is a methyltransferase that induces histone H3 lysine 27 trimethylation (H3K27me3) and functions as an oncogenic factor in many cancer types. Its role in renal epithelial-mesenchymal transition (EMT) remains unknown. In this study, we found that EZH2 and H3K27me3 were highly expressed in mouse kidney with unilateral ureteral obstruction and cultured mouse kidney proximal tubular (TKPT) cells undergoing EMT. Inhibition of EZH2 with 3-deazaneplanocin A (3-DZNeP) attenuated rena… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
46
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 48 publications
(47 citation statements)
references
References 61 publications
1
46
0
Order By: Relevance
“…Ezh2 has been described as having an important role in coordinating cell differentiation in embryonic stem (ES) cells (39,40), mesenchymal stem cells (41)(42)(43), hematopoietic stem cells (44,45), and also in various types of cancer (46,47). Inhibition of Ezh2 has been reported to prevent renal fibroblast activation (48), though more recently the same group reported that Ezh2 acts in epithelial cells to promote fibrosis (49). We confirmed by qPCR that Ezh2 was upregulated at day 2 after Bi-IRI as compared with baseline (day 0) and that its expression downtrended by day 14 (Figure 7C).…”
Section: Resultsmentioning
confidence: 99%
“…Ezh2 has been described as having an important role in coordinating cell differentiation in embryonic stem (ES) cells (39,40), mesenchymal stem cells (41)(42)(43), hematopoietic stem cells (44,45), and also in various types of cancer (46,47). Inhibition of Ezh2 has been reported to prevent renal fibroblast activation (48), though more recently the same group reported that Ezh2 acts in epithelial cells to promote fibrosis (49). We confirmed by qPCR that Ezh2 was upregulated at day 2 after Bi-IRI as compared with baseline (day 0) and that its expression downtrended by day 14 (Figure 7C).…”
Section: Resultsmentioning
confidence: 99%
“…Ezh2 has been described to have an important role in coordinating cell differentiation in embryonic stem cells (35,36), mesenchymal stem cells (37-39), hematopoietic stem cells (40,41), and also in various types of cancer (42,43). Inhibition of Ezh2 has been reported to prevent renal fibroblast activation (44), though more recently the same group reported that Ezh2 acts in epithelial cells to promote fibrosis (45). We confirmed by qCPR that Ezh2 is upregulated at day 2 after Bi-IRI as compared to baseline (day 0) and its expression downtrends by day 14 (Figure 6C).…”
Section: Differential Expression Of Transcription Factors and Secretementioning
confidence: 99%
“…Similarly, increased EZH2 levels have been detected in those two cell types in kidney biopsy samples of patients with focal segmental glomerulosclerosis and IgA nephropathy, but not with minimal change disease (Zhou et al, 2016) ( Table 3 ). Mechanistic studies showed that downregulation of EZH2 by inhibitors or siRNA reduces the activation of renal interstitial fibroblasts and epithelial-to-mesenchymal transition ( EMT ) of renal tubular cells in vitro ; treatment with the EZH2 inhibitor 3-deazaneplanocin A (3-DZNeP) also attenuates UUO-induced renal fibroblast activation, partial EMT and fibrosis in mice (Zhou et al, 2016; Zhou et al, 2018a). The antifibrotic actions of EZH2 blockade are associated with dephosphorylation of multiple profibrotic receptors, including epidermal growth factor receptor and platelet derived growth factor receptor and inactivation of several intracellular signaling pathways, including Smad3, signal transducer and activator of transcription 3 (STAT3), extracellular signal-regulated kinase ½ (ERK1/2) and AKT (Vignais et al, 1996; Wang et al, 2005; Zhou et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…The antifibrotic actions of EZH2 blockade are associated with dephosphorylation of multiple profibrotic receptors, including epidermal growth factor receptor and platelet derived growth factor receptor and inactivation of several intracellular signaling pathways, including Smad3, signal transducer and activator of transcription 3 (STAT3), extracellular signal-regulated kinase ½ (ERK1/2) and AKT (Vignais et al, 1996; Wang et al, 2005; Zhou et al, 2016). Moreover, we found that EZH2 expression is required for renal epithelial cells arrested at the G2/M phase of the cell cycle (Zhou et al, 2016; Zhou et al, 2018a) to change into a cell phenotype that is able to produce and release an excessive amount of growth factors and cytokines, thereby inducing the transition of fibroblasts into myofibroblasts (Grande et al, 2015; Lovisa et al, 2015). As development of partial EMT in renal epithelial cells is driven by Snail1 and Twist, two transcriptional factors, we also examined the role of EZH2 in the regulation of their expression following UUO injury.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation